Methylprednisolone treatment in children with nephrotic primary focal segmental glomerulosclerosis - Sauwalak Opastirakul (2018)
Objective: To examine the effectiveness of pulse methylprednisolone in children with nephrotic primary focal segmental glomerulosclerosis. Material and Method: Medical records of children, who were treated with a pulse methylprednisolone regimen for nephrotic syndrome resulting from primary focal segmental glomerulosclerosis between 1987 and 2005, were retrospectively reviewed. The age,gender, urine protein, serum creatinine, and glomerular filtration rate at the onset of nephrotic syndrome were recorded. Urine protein, serum creatinine, glomerular filtration rate, and percentile of height before and after methylprednisolone treatment were compared. Results: There were six patients (4 male, 2 female) in the present report. The mean age at onset was 9.5 ± 2.2 years. Hypertension was noted in four patients and mild renal insufficiency in three. All patients had nephrotic-ranged proteinuria at onset and they were initially treated with prednisolone. Two were steroid-dependent and four were steroid-resistant. All of the steroid resistant cases were also resistant to oral cyclophosphamide. After methylprednisolone treatment, remission of proteinuria was noted in five patients (83%) (2 complete, 3 partial). Mean duration to remission was 20.8 weeks. There were no significant changes in serum creatinine (p = 0.43), GFR (p = 0.78) and percentile of height before and after treatment. No hypertension or cardiac arrhythmia was detected during methylprednisolone administration. The follow-up period after completion of the methylprednisolone regimen was 19.5 ± 15.2 months (range 4-36 months). The clinical course of five patients with remission was characterized by sustained remission in three patients. Two patients relapsed at 2 and 8 months after treatment. Conclusion: Methylprednisolone was effective and safe in treating nephrotic children with primary focal segmental glomerulosclerosis. There was a high incidence of relapse shortly after the cessation of treatment. However, a larger number of patients and longer period of follow-up are needed to confirm this conclusion.